Enfrentando a dor na anemia falciforme: uma proposta de avaliação e intervenção psicológica com crianças - Oliveira, Christyne Gomes Toledo de (2013)
Sickle Cell Anemia (FA) has pain as its main symptom, leading to repeated hospitalizations and limitations that may impair motor, cognitive, social and emotional child development, and that requires adjustments in routine. The way children deal with pain and disease changes the clinical picture, so it is important to study the coping strategies (coping) in a developmental perspective. This is the proposal of the Motivational Theory of Coping (MTC), which defines coping as how people adapt to stressful situations, regulating behavior, emotion and motivational orientation, in order to maintain, restore or repair basic psychological needs of relationships, competence and autonomy. Coping is analyzed as a hierarchical system, with "coping families" related to the outcome in the adaptive process, such as: (a) positive - selfconfidence, seeking support, problem solving, seeking information, accommodation and negotiation, and (b ) negative - delegation, isolation, helplessness, escape, submission and opposition. Based on MTC and considering the lack of national studies with this population, this study describes and analyzes the process of coping with pain in 11 children with SCA (8- 10 years old), supporting a proposed psychological intervention. In the Clinic of Pediatric Hematology at a university hospital, they answered individually to the Protocol for SCA pain assessment (PAPIM); theStress Scale for children; the Revised Faces Scale; the specially adapted Computerized Instrument for Evaluating Straegies Facing Hospitalization (AEHcomp-Pain) and a Pain Diary. Mothers filled: the Protocol for SCA pain assessment (PAPIM); the Behavioral Inventory for Children and Adolescents between 6 and 18 years (CBCL 6-18 years); Anamneses’ Script for psychosocial data, history of illness and pain; Brazil Economic Classification Criteria; and the Protocol of Psychosocial Risk Index by Rutter. AEHcomp-Pain was applied in the pre and post-test to assess coping, identifying coping strategies [CS]: distraction, rumination, strategies planning, acceptance, seeking comfort, emotional regulation, avoidance, bargaining, asking others, cognitive restructuring, passivity, complaining, social withdrawal and blaming others. Most children were not behind in school, but were at a "moderate" psychosocial risk. Only 36.4% were diagnosed early. All had comorbidities and felt pain, in spite of medication. There was agreement among children and mothers in the frequency and location of pain, and significant differences in the assessment of the type of pain and perception of the intensity of the last episode of pain having been stronger or not than the previous. A third of the children showed signs of stress, mainly related to psychological reactions. On the CBCL, most were referred to as clinical on the scales of Total Competence, Total of Problems and Internalizing Problems. In AEHcompPain the highest proportion of not facilitating behaviors of pain coping and CS were: rumination, planning strategies, seeking comfort, acceptance, emotional regulation and passivity, and in the Accommodation families of coping, followed by Submission and Problem solving. The stressors were perceived as a challenge to autonomy and relationship, and then to Competence. This coping analysis supported the development of the Psychological Intervention Program for Children with Sickle Cell Anemia (PIPCAF), for the promotion or maintenance of the behavioral repertoire for pain control, the adaptive CS and the perception of the stressor as a challenge, and minimization of maladaptive CS including the Diary of Pain. PIPCAF was applied in 7 children, in 4 steps, with 7 weekly sessions, in groups: Step 1 - Integration (2 sessions) - to establish rapport, trust in the group and the therapeutic contract; Step 2 - Identification and expression of feelings (2 sessions) - focused on self-observation, identification and expression of feelings and thoughts about pain and disease; Step 3 - psychotherapeutic play - "facing the pain" (2 sessions) - to identify and analyze everyday situations that generate fear and stress, causing / increasing the pain, and to teach CS, with a "board"game, specially designed with distraction techniques, training in information seeking , social support, problem solving strategies and social skills, and Stage 4 - Closure and self-assessment (1 session) in order to assess the satisfaction of the child and encourage the use of the techniques of prevention and management of painful episodes. At post-test, there was significant increase in the proportion of facilitative behaviors and adaptive CS, like planning strategies and a decrease of not facilitating behaviors and maladaptive CS, such as rumination. There was significant difference in the Problem solving and Submission, with a significant increase in the perception of the stressor as a challenge to competence and decrease in the perception of it as a threat to competence and autonomy. Data suggest that PIPCAF contributed to expand the behavioral repertoire for pain management, increasing perceived control of the stressful situation, by planning strategies or emotional regulation, changing the sense of competence. Theoretical and methodological contributions to the study of pain coping in children are, thus, presented, in view of the MTC, and for the analysis of the assessment and psychological intervention in the context of chronic illness.